A first glimpse into the biogeographic affinities of the shallow benthic communities from the sub-Antarctic Crozet archipelago - Jossart, Quentin; Lelièvre, Yann; Kelch, Andreas; Figuerola, Blanca; Moreau, Camille V. E.; Di Franco, Davide; Maxwell, Jamie; Verheye, Marie L.; Mackenzie, Melanie; Downey, Rachel; Rosenfeld, Sebastián; Hourdez, Stéphane; et al. (Frontiers in Ecology and Evolution, 2024)
Sub-Antarctic islands are expected to show a high degree of endemicity due to their remoteness. However, biogeographic affinities in the sub-Antarctic remain poorly understood, especially in the marine realm. Sub-Antarctic islands being at the crossroads between Antarctic and cold temperate regions, biodiversity characterization and biogeographic analyses are a priority for monitoring and rapidly assessing variations associated with environmental changes. One underexplored sub-Antarctic area is Crozet, a protected archipelago located halfway between Antarctica and South Africa. In this study, we investigated the shallow-water Crozet macrofaunal diversity, distribution patterns and biogeographic affinities based on the examination of fieldwork specimens via a thorough morphological identification and a genetic characterisation. The resulting dataset provides an important baseline for further studies and conservation strategies, compiling the first genetic and taxonomic database for the Crozet archipelago. In total, 100 morphotypes were found, belonging to nine different phyla, among which arthropods (32), molluscs (18) and echinoderms (17) were the richest. Forty-seven morphotypes were identified to the species level, among which 20 were reported in Crozet for the first time. This confirms that Crozet is a poorly known region, even compared to other sub-Antarctic areas. A large proportion of species (62%) had circum Southern Ocean or circum sub-Antarctic distributions. These species were mostly shared with Kerguelen (72%), the Magellan Province (64%), and Prince Edward Islands (64%), confirming the patterns found in macroalgae and specific macrofaunal groups. However, this large-distribution statement needs to be counterbalanced by the detection (genetic data) of more restricted distributions than expected in four study cases (the tanaid Apseudes spectabilis, the nudibranch Doris kerguelenensis, the polychaete Neanthes kerguelensis and the chiton Hemiarthrum setulosum). Considering that most morphotypes had no genetic data available from other regions, the proportion of morphotypes with restricted distribution is likely to increase alongside future investigations. In addition, we also found a few cases of unrecognized diversity that might lead to the descriptions of new species, some likely to be endemic to Crozet (e.g., within the polychaete genus Harmothoe and the bryozoan genus Antarctothoa). Altogether, this stresses the need to maintain conservation efforts in Crozet and pursue integrative investigations in order to highlight and protect its unusual diversity.